The relationship between moral sensitivity and prosocial behavior in college students: the mediating roles of moral disengagement and reciprocity norms - Zhiyong Li; Zhiyong Li; Danqi Wang; Junhe Liao; Zhibin Jin (Frontiers in Psychology)
IntroductionThis study examined the relationship between moral sensitivity and prosocial behavior, as well as the mediating role of moral disengagement and reciprocity norms.MethodsTotally 567 college students completed Dispositional Moral Sensitivity Questionnaire, Moral Disengagement Scale for Chinese Students, Reciprocity Norm Scale, Prosocial Tendencies Measure for Adolescent.ResultsThe results showed that, moral disengagement and reciprocity norms played multiple mediating roles between moral sensitivity and prosocial behavior. Specifically, moral sensitivity affected prosocial behavior through the independent mediating effect of moral disengagement, reciprocity norms, as well as the chain mediating effect of moral disengagement and reciprocity norms.DiscussionIn summary, this study reveals the mechanism underlying the relationship between moral sensitivity and prosocial behavior, which has certain theoretical and practical significance for promoting college students’ prosocial behavior from the perspective of moral sensitivity.